2012
DOI: 10.5090/kjtcs.2012.45.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Coronary-Bronchial Artery Fistula Manifested by Hemoptysis and Myocardial Ischemia in a Patient with Bronchiectasis

Abstract: A coronary-bronchial artery fistula is a very rare congenital anomaly of the coronary artery whose etiology and pathogenesis have not yet been clarified. Most patients with coronary-bronchial fistulas are asymptomatic; however, some patients present with congestive heart failure, infective endocarditis, myocardial ischemia induced by a coronary steal phenomenon, or rupture of an aneurysmal fistula. Furthermore, patients with a coronary-bronchial artery fistula rarely manifest life-threatening hemoptysis due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…They proposed that 2 factors regulate the reopening and growth of arterial communications: disequilibrium of the pressure gradient between the 2 arteries and obstruction of the coronary arteries. Additionally, several case series have implied the possibility of a relationship between coronary-bronchial artery fistula and known bronchiectasis [2,5]. Similar to the patients who have previously been described, our patient also suffered from bronchiectasis.…”
Section: Discussionsupporting
confidence: 82%
“…They proposed that 2 factors regulate the reopening and growth of arterial communications: disequilibrium of the pressure gradient between the 2 arteries and obstruction of the coronary arteries. Additionally, several case series have implied the possibility of a relationship between coronary-bronchial artery fistula and known bronchiectasis [2,5]. Similar to the patients who have previously been described, our patient also suffered from bronchiectasis.…”
Section: Discussionsupporting
confidence: 82%
“…Clinical presentation of patients with CBF depends on the degree of left to right shunt and the concomitant disease process in the patients. Said et al reported that chest pain was the most frequent symptom (63%) that was mainly due to a coronary steal phenomenon [8,10], hemoptysis (26%), Dyspnea (19%). Asymptomatic disease occurred only in (19%) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Said et al reported that chest pain was the most frequent symptom (63%) that was mainly due to a coronary steal phenomenon [8,10], hemoptysis (26%), Dyspnea (19%). Asymptomatic disease occurred only in (19%) [10]. Our patient was admitted for exertional dyspnea and pleuritic chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…A Coronary bronchial artery fistula [CBF] is detected in 0.18% of patients who undergo routine coronary angiography [2]. When the coronary fistula drains into the right side of the heart, the volume load is increased to the right heart as well as to the pulmonary vascular bed, the left atrium, and left ventricle.When the fistula drains into the left atrium or the left ventricle, there is volume overloading of these chambers but no increase in the pulmonary blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports [2] have proposed that patients with a coronary-bronchial artery fistula need aggressive treatment, including embolization, in order to prevent lethal complications such as aneurismal rupture or infective endocarditis. Some advocate closure of coronary artery fistulae even in asymptomatic patients [4].…”
Section: Discussionmentioning
confidence: 99%